Particle swarm optimization to solve the ITC2007 examination timetabling problem - Ee, Jun Jiang (2014)
The educational institute has been annoyed by timetabling problem for many years. The timtabling is difficult due to large amount Of subject/exams to be allocated into certain timeslots at the same time fulfill all the hard constraints and some of the soft constraints (constraints are requirements of the timetable). In the timetabling research, there are various techniques/ algorithm has been used to solve the problem. However, most of them are applied to solve simpler timetabling problem which doesn't consider room capacity as constraints (or simplified the room capacity factor). In this thesis, an examination timetabling dataset that consider room capacity will be used which named Seconds International Timetabling Competition (ITC 2007); ITC, 2007 has very well defined constraints and it is more completed compared to other dataset. One chosen technique which is Particle Swarm Optimization will be used to solve the ITC 2007 examination timetabling problem.